2001
DOI: 10.1079/bjn2001377
|View full text |Cite
|
Sign up to set email alerts
|

Daily dietary intake of chromium in southern Spain measured with duplicate diet sampling

Abstract: We measured daily dietary Cr intake in southern Spain by sampling duplicate diets for seven consecutive days in different population groups. Cr was determined by electrothermal atomization±atomic absorption spectrometry. The samples were mineralized in a digestion block with HNO 3 , HClO 4 and V 2 O 5 . A total of 161 duplicate diets from twenty-three subjects were analysed, and mean levels of Cr intake ranged from 9´39 to 205´16 mg/d. Mean Cr intake (100 mg/d) was similar to levels found for most other countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
3
15
1
Order By: Relevance
“…These differences among the total Cr content in cereals and pulses in different studies could be due to variations in the soil Cr content, as well as the method of determination of Cr. A different study [29] reported a statistically significant correlation between Cr and the protein/carbohydrate content of the diet and energy intake, a finding that was not observed by us. The Cr content in chickpea reported by Cabrera et al [17] was 0.012 mg/100 g, lower than the value reported by the current study.…”
Section: Cr Content and Bioaccessibility From Cereals And Pulsescontrasting
confidence: 76%
“…These differences among the total Cr content in cereals and pulses in different studies could be due to variations in the soil Cr content, as well as the method of determination of Cr. A different study [29] reported a statistically significant correlation between Cr and the protein/carbohydrate content of the diet and energy intake, a finding that was not observed by us. The Cr content in chickpea reported by Cabrera et al [17] was 0.012 mg/100 g, lower than the value reported by the current study.…”
Section: Cr Content and Bioaccessibility From Cereals And Pulsescontrasting
confidence: 76%
“…The average daily dietary ingestion of total Cr in Canada is 13.3–16.9 μg for children ages 0.5–4 years, 18.9–21.6 μg for children ages 5–11 years, and 27.3 μg for adults (CEPA 1999). The average daily dietary ingestion of total Cr for an adult is 25–224 μg in the United States (ATSDR 2000), 100 μg in Spain (Garcia et al 2001), 59.9 μg in India, and 224 μg in Japan (Iyengar et al 2002). A chronic oral reference dose of 3 μg/kg/day is given for ingestion of Cr(VI) (U.S EPA 1998).…”
Section: Discussionmentioning
confidence: 99%
“…1. García et al (2001a) measured Cr dietary intake in southern Spain by sampling duplicate diets for seven consecutive days in different population groups that ranged between 9.39 and 205.16 lg/day with a mean of 100 lg/day. These results are similar to levels found in other countries (Ashton et al, 2003;Bocio, Nadal, & Domingo, 2005;Santos, Lauria, & Da Silveira, 2004) but higher to the range recommended by the USA Institute of Medicine (2002).…”
Section: Cr Levels In Convenience and Fast Foodsmentioning
confidence: 99%
“…The remaining parts were homogenized in a blender and the total amount of food weighed. Three aliquots of approximately 100 g were dried in a microwave oven under controlled temperature conditions (García et al, 2001a). Each dried aliquot sample was again homogenized in the blender and three portions of 0.250 g of sample was treated with 5 mL of 65% HNO 3 and a few micrograms of V 2 O 5 (as a catalyst) in Pyrex tubes placed in an acid digestion block, first it was heated at 60°C for 30 min and then, at 120°C for 60 min.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
See 1 more Smart Citation